The Effectiveness of Cognitive Behavioral Therapy (CBT) and Recreational Activities on Psychological Morbidities and Quality of Life (QOL) in Traumatic Spinal Cord Injury: A Pilot Study an Original Research Article (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2026)
BACKGROUND: Spinal Cord Injury (SCI) presents with life changing consequences altering the physical, social, vocational aspects of a person at the same time leading to multiple psychological morbidities. Depression, anxiety, and Post Traumatic Stress are the three most common psychological issues seen in SCI population. Alterations to basic physiologic functions, intense emotions, disruption of social relationships, and barriers to participating in their usual activities – leads to a compromise in their quality of life (QoL). Cognitive Behavioural Therapy administered along with recreational activities could prove to an effective mode of intervention for better mental health and QoL of traumatic SCI patients.   OBJECTIVES: To reduce stress, anxiety and depression levels in Traumatic Spinal Cord Injury patients and to improve their Quality of Life through CBT and recreational activities.  STUDY DESIGN: Pre-Post test experimental design.  METHODS: A total of 30 subjects were taken for the study as per the inclusion criteria, outcome measures used were DASS-21 and WHOQOL-BREF. Total duration of therapy was 6 weeks. 1 session for 2 hours per week was taken for initial 3 weeks. In the last 3 weeks 2 sessions per week for 2 hours duration was administered. Each session was followed by 15 mins of recreational activities. Therapy was administered in a group mode. RESULTS: Wilcoxon signed rank test revealed that there was significant improvement in DASS scores post intervention (Z= -4.183, p=
Keywords: Spinal Cord Injury, Post Traumatic Stress Disorder, Cognitive Behavioral Therapy, Quality of Life.